2013
DOI: 10.1016/j.urology.2013.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Characterization of Human Male Urethral Smooth Muscle: An In Vitro Approach

Abstract: The results provide evidence that urethral smooth muscle is under the control of endogenous compounds, such as adrenergic agonists (norepinephrine and phenylephrine), vasoactive peptides, prostagladins, NO/cyclic GMP, and acetylcholine, assumed to influence micturition at the peripheral level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…In the organ bath-assay in vitro we demonstrated that the PDE5 inhibitor vardenafil, but also the sGC stimulator BAY 41–2272, significantly and dose-dependently reduced noradrenaline-induced spontaneous oscillations of isolated rat ureter. These data are in line with the recently published data of Kedia et al (2013), Liatsikos et al (2013), and Miyaoka et al (2014)[ 39 , 40 , 41 ], showing a significant and concentration-dependent relaxation in human ureteral tissue with the NO-donnor sodiumnitroprusside (SNP), the PDE5 inhibitors vardenafil and sildenafil [ 40 , 41 ] and the sGC stimulator BAY 41–2272 [ 39 ]. In human ureteral tissue, the relaxing effects of vardenafil were also accompanied by cGMP increase, which suggests a cGMP-driven mode of action [ 41 ].…”
Section: Discussionsupporting
confidence: 88%
“…In the organ bath-assay in vitro we demonstrated that the PDE5 inhibitor vardenafil, but also the sGC stimulator BAY 41–2272, significantly and dose-dependently reduced noradrenaline-induced spontaneous oscillations of isolated rat ureter. These data are in line with the recently published data of Kedia et al (2013), Liatsikos et al (2013), and Miyaoka et al (2014)[ 39 , 40 , 41 ], showing a significant and concentration-dependent relaxation in human ureteral tissue with the NO-donnor sodiumnitroprusside (SNP), the PDE5 inhibitors vardenafil and sildenafil [ 40 , 41 ] and the sGC stimulator BAY 41–2272 [ 39 ]. In human ureteral tissue, the relaxing effects of vardenafil were also accompanied by cGMP increase, which suggests a cGMP-driven mode of action [ 41 ].…”
Section: Discussionsupporting
confidence: 88%
“…A cAMP‐dependent pathway has been suggested to be involved in the relaxant response in urethra . We demonstrated here that both PGE 2 and CP‐533,533 increased cAMP accumulation in urethral tissues of rats in a concentration‐dependent manner.…”
Section: Discussionmentioning
confidence: 49%
“…A cAMP-dependent pathway has been suggested to be involved in the relaxant response in urethra. 9,10 We demonstrated here that both PGE 2 and CP-533,533 increased cAMP accumulation in urethral tissues of rats in a concentration-dependent manner. Further, at the concentrations of PGE 2 and CP-533,536 that significantly raised cAMP levels in urethral tissues, the compounds also induced relaxation of the tissue.…”
Section: Discussionmentioning
confidence: 59%
“…; Chen & Brading, ; Andersson, ; Kedia et al . ). Genes encoding all three α1 adrenoceptors were expressed in sorted USMCs (Fig.…”
Section: Resultsmentioning
confidence: 97%